2008
DOI: 10.1002/da.20356
|View full text |Cite
|
Sign up to set email alerts
|

The Penn State Worry Questionnaire: psychometric properties of the Korean version

Abstract: The factor structure and concurrent validity of the Penn State Worry Questionnaire (PSWQ) were examined in two college student samples in Korea. We demonstrated method effects due to the inclusion of negatively keyed items. Confirmatory factor analyses supported the single-factor model with method factor. This indicates that the Korean version of the PSWQ (K-PSWQ) can be contaminated by method effects and response patterns are different between positively worded and reverse-scored items. Thus, the relevance of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
37
1
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 32 publications
(45 citation statements)
references
References 32 publications
(48 reference statements)
6
37
1
1
Order By: Relevance
“…This is consistent with some previous studies, which found that the one-factor-withmethod-effect model provided a better fit than the two-factor structure (Brown, 2003;Hazlett-Stevens et al, 2004;Lim et al, 2008). In the method-effect model, the covariance of the 5 reversed items is assumed to be due to substantively irrelevant method effects, not some latent factors.…”
Section: Discussionsupporting
confidence: 90%
See 4 more Smart Citations
“…This is consistent with some previous studies, which found that the one-factor-withmethod-effect model provided a better fit than the two-factor structure (Brown, 2003;Hazlett-Stevens et al, 2004;Lim et al, 2008). In the method-effect model, the covariance of the 5 reversed items is assumed to be due to substantively irrelevant method effects, not some latent factors.…”
Section: Discussionsupporting
confidence: 90%
“…Later, Hazlett-Stevens et al(2004) found that the five reverse-direction PSWQ items do not make up a separate worry construct, but rather, contain an underlying factor of negative wording method. This result has recently been replicated in a sample of Korean college students (Lim et al, 2008). However, a flaw in the aforementioned studies (Brown, 2003;Hazlett-Stevens et al, 2004;Lim et al, 2008) is that the two-factor model and one-factor model with method effect have indistinguishable goodness of fit.…”
Section: Introductionmentioning
confidence: 78%
See 3 more Smart Citations